2023
DOI: 10.1021/acssuschemeng.2c07629
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of V2O5 Nanoribbon–Reduced Graphene Oxide Hybrids as Stable Aqueous Zinc-Ion Battery Cathodes via Divalent Transition Metal Cation-Mediated Coprecipitation

Abstract: Aqueous zinc-ion batteries (AZIBs) are an emerging sustainable and safer technology for large-scale electrical energy storage. Here, we report the synthesis of hybrid materials consisting of V2O5 nanoribbons (NRs) and reduced graphene oxide (rGO) nanosheets as AZIB cathode materials by divalent metal cation-mediated coprecipitation. The divalent metal ions M2+ (Zn2+ and Mn2+) effectively neutralize the negative charges on the surface of microwave-exfoliated crystalline V2O5 NRs and graphene oxide (GO) nanoshee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Moreover, a recent publication that used cations to assemble α-V 2 O 5 and rGO found that assembling cations with higher oxidation states acted as more stable pillars to support the V 2 O 5 layers and the interface between V 2 O 5 and rGO. 56 In the Na-ion system, the Na-LVO/rGO heterostructure showed the highest initial capacity of 99 mAh g −1 compared to the 94 and 49 mAh g −1 capacities shown by the Li-LVO/rGO and K-LVO/rGO structures. It also showed an impressive 95% capacity retention (94 mAh g −1 capacity) after 100 discharge− charge cycles, compared to the 84% retention observed for the Li + ion assembled material.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, a recent publication that used cations to assemble α-V 2 O 5 and rGO found that assembling cations with higher oxidation states acted as more stable pillars to support the V 2 O 5 layers and the interface between V 2 O 5 and rGO. 56 In the Na-ion system, the Na-LVO/rGO heterostructure showed the highest initial capacity of 99 mAh g −1 compared to the 94 and 49 mAh g −1 capacities shown by the Li-LVO/rGO and K-LVO/rGO structures. It also showed an impressive 95% capacity retention (94 mAh g −1 capacity) after 100 discharge− charge cycles, compared to the 84% retention observed for the Li + ion assembled material.…”
Section: Resultsmentioning
confidence: 91%
“…BVO preintercalated with Mg 2+ ions maintains a large interlayer spacing, , which can be important for charge storage properties as demonstrated in this work. Moreover, a recent publication that used cations to assemble α-V 2 O 5 and rGO found that assembling cations with higher oxidation states acted as more stable pillars to support the V 2 O 5 layers and the interface between V 2 O 5 and rGO …”
Section: Results and Discussionmentioning
confidence: 99%
“…Presently, vanadium-based oxides especially for V 2 O 5 have stood out as promising cathode materials for AZIBs stemming from their unique layered structure and rich oxidation state of vanadium. Based on the two merits, V 2 O 5 can provide a channel for the diffusion of Zn 2+ and deliver a remarkable theoretical specific capacity of 589 mAh g –1 . , However, owing to the strong electrostatic interaction between Zn 2+ and the VO x layer, V 2 O 5 suffers from poor diffusion rate and instability of layered structure, thus deteriorating the electrochemical performance of AZIBs. In 2016, Nazar and co-workers first reported a bilayered σ-Zn 0.25 V 2 O 5 ·nH 2 O nanobelts with zinc ions and water molecules preintercalation and demonstrated that the guest-ions could serve as “pillars” to significantly stabilize the layered structure and further improve the capacity and cycling stability of V 2 O 5 . Since then, the guest preintercalation strategy gradually began to be widely used to enhance the electrochemical performance of vanadium oxide cathodes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a hybrid electrocatalyst applying materials with OER and ORR capabilities should be used as an integrated form to have synergetic effects. 3–5 Recently, some reports have focused on bimetallic electrocatalysts, such as Fe/Fe 3 C in N-doped porous carbon, 6 CoFe nanoparticles on N-doped carbon sheets (CoFe@NCS), 7 FeCo alloy nanoparticles in carbon layers, 8,9 Co 0.25 Ni 0.75 alloy/N-doped carbon nanotube, 10 N-Co 0.8 Fe 0.1 Ni 0.1 S x , 11 Pd nanoparticles/F, N codoping graphene composite, 12 Mn-incorporated Co 3 O 4 , 13 carbon dots bridge NiO and Mn 2 O 3 (NiO–Mn 2 O 3 -CDs), 14 V 2 O 5 nanoribbon/reduced graphene oxide, 15 LiCoO 1.8 F 0.2 , 16 ionic liquid-derived FeCO alloys encapsulated in N-doped carbon framework, 17 Co–N-doped carbons embedded with ultrafine CoFe/Co nanoparticles, 18 FeCo alloy nanoparticles encapsulated in hollow N-doped carbon, 19 N-doped Fe 3 C containing carbon material, 20 and others.…”
Section: Introductionmentioning
confidence: 99%